Answer:
The answer is below
Explanation:
The equation x² - 3x - 2 cannot be factorized, I think the correct question is:
factorize x² - 3x + 2
Solution:
A quadratic equation is a polynomial equation of the second degree (that is there is at least one term with a degree of 2).
The standard form of a quadratic equation is given by the equation:
ax² + bx + c = 0
Where a, b, and c being constants and x is the unknown variable.
Given:
x² - 3x + 2
= x² - 2x - x + 2
= x(x - 2) -1(x - 2)
= (x - 1)(x - 2)